Analysis of Temperature Stability and Accuracy on the Design of Thermometer Calibrator Based on Fuzzy Logic And On/Off Control - Yunik Pujiastuti; Andjar Pudji; Singgih Yudha Setiawan; Farid Amrinsani; Khongdet Phasinam (Journal of Electronics, Electromedical Engineering, and Medical Informatics, 2022)
A thermometer is a medical device used to measure body temperature. To maintain the accuracy of the thermometer measurement results, periodic calibration is required. Calibration is an activity to determine the conventional correctness of the indicator values of measuring instruments and measuring materials by comparing them with measurement standards that can be traced to national and international standards for units of measure and/or international and certified reference materials. Based on the results of the identification of chronological problems that have been observed, a body thermometer that measures body temperature is needed so and a calibrator is needed to maintain the accuracy of the thermometer. The purpose of this study was to analyze the Temperature Stability and Accuracy of the Body Thermometer Calibrator Based on on-Off Control and Fuzzy Logic Control. The contribution of this research to this tool will use the development of a fuzzy logic control method to produce temperature stability in the Body Thermometer Calibrator (Digital). The method used in this study used fuzzy control and on-off control. The results of this study from the suitability test obtained a maximum error of 0.2% in the fuzzy control and 0.6% in the On-Off control.  The average rise time difference for the two controls was 13.53 Seconds. The average settling time difference is 130.46 seconds. The results of this study can be concluded that the Fuzzy System is better than the On / Off system so the Fuzzy system is more suitable for thermometer calibration media.